The Myosin Motor Domain-Containing Chitin Synthases Are Involved in Cell Wall Integrity and Sensitivity to Antifungal Proteins in Penicillium digitatum - Gandía, Mónica; Garrigues, Sandra; Bolós, Begoña; Manzanares, Paloma; Marcos, Jose F. (Frontiers in Microbiology, 2019)
Penicillium digitatum is the main postharvest pathogen of citrus fruit and is responsible for important economic losses in spite of the massive use of fungicides. The fungal cell wall (CW) and its specific component chitin are potential targets for the development of new antifungal molecules. Among these are the antifungal peptides and proteins that specifically interact with fungal CW. Chitin is synthesized by a complex family of chitin synthases (Chs), classified into up to eight classes within three divisions. Previously, we obtained and characterized a mutant of P. digitatum in the class VII gene (ΔchsVII), which contains a short myosin motor-like domain (MMD). In this report, we extend our previous studies to the characterization of mutants in chsII and in the gene coding for the other MMD-Chs (chsV), and study the role of chitin synthases in the sensitivity of P. digitatum to the self-antifungal protein AfpB, and to AfpA obtained from P. expansum. The ΔchsII mutant showed no significant phenotypic and virulence differences with the wild-type strain, except in the production and morphology of the conidia. In contrast, mutants in chsV showed a more dramatic phenotype than the previous ΔchsVII, with reduced growth and conidia production, increased chitin content, changes in mycelial morphology and a decrease in virulence to citrus fruit. Mutants in chsVII were specifically more tolerant than the wild type to nikkomycin Z, an antifungal inhibitor of chitin biosynthesis. Treatment of P. digitatum with its own antifungal protein AfpB resulted in an overall reduction of the chitin synthase genes expression. The mutants corresponding to MMD chitin synthases had a differential sensitivity to the antifungal proteins AfpA and AfpB, ΔchsVII being more susceptible than its parental strain and ΔchsV slightly more tolerant despite its reduced growth in liquid broth. Taken these results together, we conclude that the myosin motor domain-containing chitin synthases affect cell wall integrity and sensitivity to antifungal proteins in P. digitatum.